Fitsbot (Fire Detection Smart Robot) Innovation in the Development of Drone Technology in Mitigation of Peat Forest Fire - Darmono; Sahid Ramandhani; Yanuar Agung Fadlullah; Khakam Ma’ruf; Surono (PT FORMOSA CENDEKIA GLOBAL, 2023)
Indonesia's forests continue to shrink due to forest fires. Indonesia's deforestation rate for 2019-2020 is 115.5 thousand hectares. The use of manual methods for forest monitoring is considered less effective because it requires a long time and a lot of resources. Natural and weather conditions affect the implementation of forest monitoring to prevent forest fires. Based on these problems, the author offers an innovation in FITSBOT (Fire Smart Robot) technology. The research method used is Research and Development (R&D) with the stages of Analysis, Design, Development, Implementation and Evaluation. The result of this research is a quadcopter with integrated artificial intelligence based on YOLO for forest monitoring. This technology is expected to facilitate forest monitoring in order to take preventive measures and early detection of forest fires.